2016
DOI: 10.1002/anie.201510847
|View full text |Cite
|
Sign up to set email alerts
|

RNA Hairpin Folding in the Crowded Cell

Abstract: Precise secondary and tertiary structure formation is critically important for the cellular functionality of ribonucleic acids (RNAs). RNA folding studies were mainly conducted in vitro, without the possibility of validating these experiments inside cells. Here, we directly resolve the folding stability of a hairpin‐structured RNA inside live mammalian cells. We find that the stability inside the cell is comparable to that in dilute physiological buffer. On the contrary, the addition of in vitro artificial cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 76 publications
(98 citation statements)
references
References 48 publications
6
90
0
Order By: Relevance
“…Experiments conducted using this technique have shown clearly that the equilibrium thermal stability and kinetics of conformational change of a given fluorescently labeled probe can vary substantially within a single cell 64, 65 , and between cells of the same type 39 . For example, the positional variability of folding kinetics and equilibrium of a mutant of phosphoglycerokinase fused to green and red fluorescent proteins in intact U2OS (mammalian) cells is clearly non-random (Figures 3A,B), and appears to correlate with supramolecular structures such as membranes or cytoskeletal fibers within the cell 55 .…”
Section: What Have We Learned From “In Vivo” Experiments?mentioning
confidence: 99%
“…Experiments conducted using this technique have shown clearly that the equilibrium thermal stability and kinetics of conformational change of a given fluorescently labeled probe can vary substantially within a single cell 64, 65 , and between cells of the same type 39 . For example, the positional variability of folding kinetics and equilibrium of a mutant of phosphoglycerokinase fused to green and red fluorescent proteins in intact U2OS (mammalian) cells is clearly non-random (Figures 3A,B), and appears to correlate with supramolecular structures such as membranes or cytoskeletal fibers within the cell 55 .…”
Section: What Have We Learned From “In Vivo” Experiments?mentioning
confidence: 99%
“…More recently, the discussion revolving around the macromolecular crowding effect includes also the consideration of nonspecific chemical (“soft”) interactions between solute and cosolvents, which are of enthalpic nature and can influence the folding stability and dynamics of biomolecules . This enthalpic contribution depends on temperature as well as on the chemical make‐up of the biomolecule, the crowder and the solvent .…”
Section: Thermodynamic Concepts Describing the Effects Of Macromolecmentioning
confidence: 99%
“…Many studies reported on the stabilizing effect of in vitro macromolecular crowding on folding equilibria, which ranges from modest to strong, [8] whereas cellularc rowding was shown to only weakly shift protein folding equilibria towards the folded state [167][168][169][170][171] or even to destabilize the folded state. [172][173][174][175][176] To explain the stabilizinga nd destabilizing effect of crowding on the folding equilibria of biomolecules, steric and nonspecific chemical ("soft") interactions between solute and cosolvent have been introduced( Figure 6).…”
Section: Thermodynamic Concepts Describing the Effects Of Macromolecumentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 The azide may be directly used for Click cyclization (see below) or, upon reduction to an amino group, for conjugation with a desired functionality via peptide chemistry. 25 Specific 5 0 -RNA functionalization can be also achieved by transcription priming, adding to the transcription mixture an initiator nucleotide that carries no triphosphate for polymerization and therefore can be used only for priming RNA synthesis at the 5 0 -end. 26,27 This protocol has been mostly used with T7-RNA-Polymerase and therefore requires guanosine conjugated via a 5 0 -phosphate with the desired functionality, as initiator nucleotide (the 5 0 -phosphate is necessary for recognition/ acceptance of the modified building block by the polymerase).…”
Section: Chain Assemblymentioning
confidence: 99%